Thermal and physicochemical properties of sugar palm fibre treated with borax - Isma'ila, Mukhtar; Leman, Zulkiflle; Ishak, Mohamad Ridzwan; Zainudin, Edi Syams (IOP Publishing, 2018)
Natural fibres are biodegradable, low-cost, and low-density materials found in many parts of the world in large quantities. The comparative properties and competitive advantages make it be a preferred material in many engineering applications. The major challenges associated with natural fibres are its low thermal stability, lack of interfacial adhesion, poor resistance to moisture and inferior mechanical properties when compared with synthetic fibres. The solution is to treat it with either alkali, silane, or other treatment methods. Specifically, alkaline treatment comes with an additional problem such as fibre degradation. Therefore, this work employed the use of borax as a treatment chemical rather than its usage as a fire retardant. This could give a treated natural fibre with mild degradation and acceptable properties. Therefore, in this research sugar palm fibre was treated with 5 w/w% borax, washed several times and dried in an oven. The treated and untreated fibres were characterized based on X-Ray Diffraction, thermal stability, and morphological analysis. The experimental results showed that the crystallinity index increased from 44.02 % to 49.56 %, while the thermal stability increased from 246.76 °C to 255.5 °C with borax treatment. The morphological investigation revealed that the surface of the treated fibre is rough with no silica deposit when compared with the untreated fibre. In conclusion, the investigation proved that treatment with the borax has a significant effect on the physicochemical properties of sugar palm fibre.